Climate Change Impacts in Bhutan: Challenges and opportunities for the agricultural sector - Parker, Louis; Guerten, Nora; Thi Nguyen, Than; Rinzin, Chimi; Tashi, Dawa; Wangchuk, Dorji; Bajgai, Yadunath; Subedi, Kiran; Phuntsho, Loday; Thinley, Namgay; Chhogyel, Ngawang; Gyalmo, Tasho; et al. (International Center for Tropical Agriculture, 2017)
This project was undertaken to examine the suitability of 8 keys crops in Bhutan under current conditions and future climate scenarios (RCP 8.5) up to 2050. This was a collaborative initiative between MoAF, CIAT and UNEP, funded through the Asia-Pacific Climate Technology Network and Finance Center (AP-CTNFC). The project had two principal objectives: Objective 1: Build capacities of key technical staff to produce suitability maps for a wider range of crops under different emission scenarios. Furthermore enhance the understanding and interpretation of uncertainties of the projections and introduce climate-resilient crop management practices in Bhutan. Objective 2: Assess the impacts of climate change on the climatic suitability of maize, rice, potato, chili and tomato growing areas in Bhutan. Share and discuss the results and implications of crop suitability studies with key stakeholders from Bhutan and relevant international agencies such as UNEP and FAO.